Overflow: Mario Levrero’s isolation in the Uruguayan dictatorship - Bello Rodríguez, Carlos (Anales de Literatura Hispanoamericana, 2014)
Framed by the context of repression and censorship imposed by the Uruguayan dictatorship (1973-1985), the production of Mario Levrero had its particular leaking point. His ‘accidental trilogy’ –formed by La ciudad, El lugar and París (written between 1966 and 1970)– gave place to the writing of Nick Carter se divierte mientras el lector es asesinado y yo agonizo, parodic nouvelle that is characterized by the irruption of humor as a useful therapy.
Keywords: interior exile; Uruguayan dictatorship; self-censorship; fantastic fiction; crime fiction.